2021
DOI: 10.1002/jlb.3ma0121-024rrrr
|View full text |Cite|
|
Sign up to set email alerts
|

Sinomenine increases adenosine A2A receptor and inhibits NF-κB to inhibit arthritis in adjuvant-induced-arthritis rats and fibroblast-like synoviocytes through α7nAChR

Abstract: Sinomenine (SIN) is a clinical drug for treating rheumatoid arthritis (RA) in China. Our previous study found SIN inhibited inflammation via alpha7 nicotinic acetylcholine receptor (α7nAChR) in macrophages in vitro. Adenosine receptor A2A has anti‐inflammatory and immunosuppressive function. However, the mechanisms of SIN acting on α7nAChR and the effect on adenosine A2A receptor (A2AR) in RA are not clear. In the present study, the effects of SIN on adjuvant‐induced‐arthritis (AIA) rats in vivo and on fibrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…et al reported that SIN (200 µM) inhibited MCP-1, IL-6, and vascular endothelial growth factor, increased A 2A R in synovial tissue of AIA rats and FLSs, and inhibited the NF-κB pathway via α7nAChR, thereby alleviating arthritis. SIN (120 mg/kg) also decreased the arthritis index in vivo [ 127 ]. Local and systemic inflammation are characteristics of rheumatoid arthritis (RA), a chronic autoimmune disease.…”
Section: Anti-inflammatory Activity and Analgesic Activitymentioning
confidence: 99%
“…et al reported that SIN (200 µM) inhibited MCP-1, IL-6, and vascular endothelial growth factor, increased A 2A R in synovial tissue of AIA rats and FLSs, and inhibited the NF-κB pathway via α7nAChR, thereby alleviating arthritis. SIN (120 mg/kg) also decreased the arthritis index in vivo [ 127 ]. Local and systemic inflammation are characteristics of rheumatoid arthritis (RA), a chronic autoimmune disease.…”
Section: Anti-inflammatory Activity and Analgesic Activitymentioning
confidence: 99%
“…Recent studies have shown that sinomenine regulated the secretion of inflammatory cytokines and macrophage subsets, and inhibited the activation of the nuclear factor-kappa B (NF-κB) pathway in fibroblast-like synoviocytes (FLS). 7,8 To date, the effects of Mag on macrophage in RA have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…et Wils., has long been known as an anti-inammatory drug. [15][16][17][18][19] SIN has been reported to inhibit the production of proinammatory mediators, such as TNF-a, nitric oxide (NO) and IL-6, both in vitro and in vivo. [20][21][22] Therefore, SIN was regarded as lead compounds in the drug research, especially for anti-inammatory medicines, while low activity had limited its clinical application.…”
Section: Introductionmentioning
confidence: 99%